CZTS solar cell with non-toxic buffer layer: A study on the sulphurization temperature and absorber layer thickness. (1st September 2020) - Prabeesh, P.; Sajeesh, V.G.; Packia Selvam, I.; Divya Bharati, M.S.; Mohan Rao, G.; Potty, S.N.
Highlights: Fabricated non-toxic CZTS solar cell with ZnS buffer layer. Investigated the effect of absorber layer thickness on the solar cell performance. Prepared phase pure CZTS film by spin coating using non-toxic chemicals. Structural refinement of CZTS was done using Rietveld refinement technique. Abstract: Cu2 ZnSnS4 solar cell has been fabricated with a non-toxic buffer layer and Al doped ZnO transparent conducting layer. A detailed material study on each layer of the solar cell has been carried out independently. The precursor films prepared by spin coating were sulphurized at different temperatures to optimize the conditions to obtain phase pure CZTS films. X-ray diffraction, Raman spectroscopy and rietveld refinement studies confirmed the phase purity of the film sulphurized at 500 °C. The optimum CZTS properties like band gap of 1.45 eV, high absorption coefficient 2 × 10 5 cm −1 and dense surface morphology were obtained for films sulphurized at 500 °C. Carrier concentration, mobility and resistivity of these films were 1 × 10 19 cm −3, 0.23 cm 2 V −1 s −1 and 2.7 Ωcm, respectively. The efficiency measurements of the cells with device structure SLG/Mo/CZTS/ZnS/AZO/Ag were carried out using absorber films with three different thicknesses. The optimized CZTS absorber layer with thickness of 1.8 µm exhibited solar cell conversion efficiency of 3.02% for an active area of 0.21 cm 2 with open-circuit voltage of 0.38 V, short-circuit current density of 17.19 mA/cm 2 and fill factor of 46%.